Defect Engineering: Can it Mitigate Strong Coulomb Effect of Mg2+ in Cathode Materials for Rechargeable Magnesium Batteries? - Fan, Zhengqing; Li, Ruimin; Zhang, Xin; Zhao, Wanyu; Pan, Zhenghui; Yang, Xiaowei (Nano-Micro Letters, 2024)
Rechargeable magnesium batteries (RMBs) have been considered a promising “post lithium-ion battery” system to meet the rapidly increasing demand of the emerging electric vehicle and grid energy storage market. However, the sluggish diffusion kinetics of bivalent Mg2+ in the host material, related to the strong Coulomb effect between Mg2+ and host anion lattices, hinders their further development toward practical applications. Defect engineering, regarded as an effective strategy to break through the slow migration puzzle, has been validated in various cathode materials for RMBs. In this review, we first thoroughly understand the intrinsic mechanism of Mg2+ diffusion in cathode materials, from which the key factors affecting ion diffusion are further presented. Then, the positive effects of purposely introduced defects, including vacancy and doping, and the corresponding strategies for introducing various defects are discussed. The applications of defect engineering in cathode materials for RMBs with advanced electrochemical properties are also summarized. Finally, the existing challenges and future perspectives of defect engineering in cathode materials for the overall high-performance RMBs are described. Highlights: 1 The underlying migration mechanism of Mg2+ in cathode materials and roles of defects in Mg2+ migration in cathode materials were studied. 2 Applications of defect engineering to Mg2+ migration in cathode materials and the strategies for introducing various defects were summarized. 3 New development directions of defect engineering in cathode materials for rechargeable magnesium battery were prospected.